Rare Case: Embolization for the Treatment of Delayed Hematuria Renal Artery Pseudoaneurysm Following Blunt Trauma - Ginanda Nabilla Hardiyanti; Ahmad Kabir, Ahmad Khairulnaim; Mustafa, Nur Liyana Mohamed; Tharek, Anas; Al-Khafiz Kamis, Mohd Fandi; Nasir Aslam, Achmad Bayhaqi; Bin Muda, Ahmad Sobri (The Interventionalist Journal, 2023)
Background: The occurrence of a renal artery pseudoaneurysm after blunt renal trauma is an infrequent complication. The occurrence of delayed bleeding is typically observed within a period of 2 to 3 weeks following an injury and is commonly attributed to the presence of an arteriovenous malformation (AVM) or pseudoaneurysm. They are frequently observed in cases of injuries of greater severity or trauma that penetrates the body. The application of angiographic catheterization is efficacious in the detection of pseudoaneurysms in the renal artery. The management of renal pseudoaneurysms necessitates the consideration of distinct clinical associations, including the location and size of the lesion as well as the presence of symptoms. Objective: The objective of this study is to provide a detailed account of the use of an angiographic catheter and embolization in the treatment of a patient afflicted with a post-traumatic renal artery pseudoaneurysm. Materials and Methods: Conducting a literature review and medical records. Results: A case of renal artery pseudoaneurysm is presented. A male individual aged 33 sought medical attention at the emergency department following a motorcycle collision and exhibited symptoms of pain in the right flank region. The individual underwent a medical intervention involving the placement of a double J stent. After a period of nearly fourteen days, the individual reported experiencing hematuria. The abdominal CT scan revealed a renal injury on the right side with an AAST grade of 4, while the renal CTA demonstrated the presence of a pseudoaneurysm. A pseudoaneurysm was observed at the renal poles on the right side through the use of an angiographic catheter. The procedure of selective embolization utilising coils was executed on the renal arteries located at the lower and middle poles of the right kidney. Conclusion: The occurrence of renal artery pseudoaneurysms is infrequent; however, it is a grave complication that may arise from renal trauma. The accurate diagnosis and effective management of pseudoaneurysms are of paramount importance due to their potential to cause severe and potentially fatal complications if left untreated. The diagnostic process for pseudoaneurysms heavily relies on the involvement of the general radiologist. Interventional radiology provides alternative minimally invasive procedures that are linked to reduced morbidity and mortality rates and have replaced surgical interventions in the management of certain conditions. Keywords: pseudoaneurysm, angiographic catheter, embolization